Exploring the Neighborhood-Level Impact of Retail Marijuana Outlets on Crime in Washington State - Thacker, John (Journal of quantitative criminology, 2023)
Objectives Since 2012, the production, sale, and use of marijuana and its derivatives for recreational consumption have been legalized in 15 states and Washington, DC, but remain controversial nationwide. Critics argue that marijuana retail outlets attract criminal activity in surrounding areas and promote social disorganization. This paper examines this issue by analyzing secondary data from Washington State, one of the first states to legalize the medical and recreational use of marijuana. Methods Using geocoded police incident reports as a proxy for criminal events, retail outlet licensing/sales data, and other contextual data, we use a difference-in-difference and other quasi-experimental techniques to model whether the opening of a recreational outlet affects crime in the surrounding neighborhoods, specifically in the cities of Seattle, Bellevue, and Tacoma. Results The analyses find modest but statistically significant increases in property crime in Census block groups containing new retail stores. Conclusions The findings from this study are consistent with some previous research that finds a link between marijuana outlets opening and an increase in neighborhood crime, but additional research is needed to further explore the association, for instance, in other states that have legalized recreational marijuana.